A Comparison of Differences Between the Systemic Pharmacokinetics of Levobupivacaine and Ropivacaine During Continuous Epidural Infusion: A Prospective, Randomized, Multicenter, Double-Blind Controlled Trial. (August 2015) - Perotti, Luciano; Cusato, Maria; Ingelmo, Pablo; Niebel, Thekla Larissa; Somaini, Marta; Riva, Francesca; Tinelli, Carmine; De Andrés, José; Fanelli, Guido; Braschi, Antonio; Regazzi, Mario; Allegri, Massimo
Abstract : BACKGROUND: Epidural infusion of levobupivacaine and ropivacaine provides adequate postoperative pain management by minimizing side effects related to IV opioids and improving patient outcome. The safety profile of different drugs can be better estimated by comparing their pharmacokinetic profiles than by considering their objective side effects. Because levobupivacaine and ropivacaine have different pharmacokinetic properties, our aim was to investigate whether there is a difference in the pharmacokinetic variability of the 2 drugs in a homogeneous population undergoing continuous epidural infusion. This double-blind, multicenter, randomized, controlled trial study was designed to compare the pharmacokinetics of continuous thoracic epidural infusion of levobupivacaine 0.125% or ropivacaine 0.2% for postoperative pain management in adult patients who had undergone major abdominal, urological, or gynecological surgery. This study is focused on the evaluation of the coefficient of variation (CV) to assess the equivalence in the systemic exposure and interindividual variability between levobupivacaine and ropivacaine and, therefore, the possible differences in the predictability of the plasmatic concentrations of the 2 drugs during thoracic epidural infusion. METHODS: One hundred eighty-one adults undergoing major abdominal surgery were enrolled in the study. Patients were randomized to receive an epidural infusion of levobupivacaine 0.125% + sufentanil 0.75 μg/mL or of ropivacaine 0.2% + sufentanil 0.75 μg/mL at 5 mL/h for 48 hours. The primary end point of this study was to analyze the variability of plasma concentration of levobupivacaine and ropivacaine via an area under the curve within a range of 15% of the CV during 48 hours of continuous epidural infusion. The CV shows how the concentration values of local anesthetics are scattered around the median concentration value, thus indicating the extent to which plasma concentration is predictable during infusion. Secondary end points were to assess the pharmacologic profile of the local anesthetics used in the study, including an analysis of mean peak plasma concentrations, and also to assess plasma clearance, side effects, pain intensity (measured with a verbal numeric ranging score, i.e., static Numeric Rating Scale [NRS] and dynamic NRS]), and the need for rescue doses. RESULTS: The comparison between the 2 CVs showed no statistical difference: the difference between area under the curve was within the range of 15%. The CV was 0.54 for levobupivacaine and 0.51 for ropivacaine ( P = 0.725). The plasma concentrations of ropivacaine approached the Cmax significantly faster than those of levobupivacaine. Clearance of ropivacaine decreases with increasing patient age. There were no significant differences in NRS, dynamic NRS scores, the number of rescue doses, or in side effects between groups. CONCLUSIONS: Considering the CV, the interindividual variability of plasma concentration for levobupivacaine and ropivacaine is equivalent after thoracic epidural infusion in adults. We found a reduction in clearance of ropivacaine depending on patient age, but this finding could be the result of some limitations of our study. The steady-state concentration was not reached during the 48-hour infusion and the behavior of plasma concentrations of ropivacaine and levobupivacaine during continuous infusions lasting more than 48 hours remains to be investigated, because they could reach toxic levels. Finally, no differences in the clinical efficacy or in the incidence of adverse effects between groups were found for either local anesthetic. Abstract : Published ahead of print May 14, 2015